2024
DOI: 10.3390/polym16020223
|View full text |Cite
|
Sign up to set email alerts
|

Significantly Enhanced Balance of Dielectric Properties of Polyvinylidene Difluoride Three-Phase Composites by Silver Deposited on K2Ni0.93Ti7.07O16 Hollandite Nanoparticles

Alexey Tsyganov,
Maria Vikulova,
Ilya Zotov
et al.

Abstract: Three-phase polymer composites are promising materials for creating electronic device components. The qualitative and quantitative composition of such composites has a significant effect on their functional, in particular dielectric properties. In this study, ceramic filler K2Ni0.93Ti7.07O16 (KNTO) with Ag coating as conductive additive (0.5, 1.0, 2.5 wt.%) was introduced into the polyvinylidene difluoride (PVDF) polymer matrix in amounts of 7.5, 15, 22.5, and 30 vol.%. to optimize the dielectric constant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Therefore, the composites filled with two or more types of fillers have been explored [ 19 , 20 ]. By introducing Ag-coated ceramic filler K 2 Ni 0.93 Ti 7.07 O 16 (KNTO) into polyvinylidene fluoride (PVDF), the dielectric constant of 2.5 wt% KNTO @ Ag/PVDF composites was 1.62 times that of KNTO-PVDF and 2.59 times of pure PVDF film [ 21 ]. Huanhuan Zhang [ 22 ] reported that the addition of two-dimensional organic modified montmorillonite (OMMT) into CNT/PVDF composites can prevent the formation of CNT conductive pathways and allow electrons to move freely in CNT clusters within a short distance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the composites filled with two or more types of fillers have been explored [ 19 , 20 ]. By introducing Ag-coated ceramic filler K 2 Ni 0.93 Ti 7.07 O 16 (KNTO) into polyvinylidene fluoride (PVDF), the dielectric constant of 2.5 wt% KNTO @ Ag/PVDF composites was 1.62 times that of KNTO-PVDF and 2.59 times of pure PVDF film [ 21 ]. Huanhuan Zhang [ 22 ] reported that the addition of two-dimensional organic modified montmorillonite (OMMT) into CNT/PVDF composites can prevent the formation of CNT conductive pathways and allow electrons to move freely in CNT clusters within a short distance.…”
Section: Introductionmentioning
confidence: 99%